IMPLEMENTASI GAMIFIKASI DALAM PLATFORM PEMBELAJARAN PEMROGRAMAN BAHASA JAVA BERBASIS WEBSITE - Saputra, Pramana Yoga; Yunianto, Dika Rizky; Rozi, Imam Fahrur; Nurhasan, Usman; Wijanarko, Eko Setio; Al Huda, Muhammad Iqbaluddin (P3M Politeknik Negeri Indramayu, 2024)
The Industry 4.0 era is characterized by a revolution involving automation and artificial intelligence, distinguishing it from previous generations. This automation is driven by machine learning, a system that enables machines to learn from experience and data. Machine learning requires strong programming skills, which are developed through effective learning processes. However, many students encounter difficulties in learning programming, particularly during the pandemic, which has hindered face-to-face instruction. These difficulties include a lack of motivation and understanding in problem-solving. To address these issues, researchers conducted a study by developing a web-based programming learning platform that implements Gamification learning methods. This technology-enhanced learning platform is specifically designed for the Java programming language and aims to enhance student motivation and understanding through online learning modules and practical exercises. The results of this study demonstrate that the use of the learning platform has a significant positive impact, as evidenced by Wilcoxon test results. The testing results show that 20 users of the system experienced improved learning outcomes. The Asymp.Sig (2-tailed) value of 0.000 indicates that there is a significant effect of using the learning platform on the Java programming learning outcomes for users..